The influence of lawan sastra ngesti mulya theachings and tax rates on tax evasion intentions - Wardani, Dewi Kusuma; Sari, Anindya Intan (Proceeding International Conference on Accounting and Finance, 2024)
This research is aimed at finding out the influence of Tamansiswa's teachings, namely Lawan Sastra Ngesti Mulya and tax rates on tax evasion intentions. Students from Tamansiswa College in Central Java Province and the Special Region of Yogyakarta were the sample population in this study. The method used in this research uses a quantitative method by distributing questionnaires to 101 respondents, while for sampling using the convenience sampling method. This study concluded that the teaching of lawan sastra ngesti mulya has a negative effect on tax evasion intentions in contrast to the tax rate variable with the results having no effect on tax evasion intentions.